Engaged Scholar(ship) in purchasing and supply management (PSM): Creative tension or squeezed in the middle?. Issue 4 (October 2019) - Bäckstrand, Jenny; Halldórsson, Árni
Abstract: Purchasing and supply management research influences practice through the advancement of knowledge and theoretical principles and is positioned as an academic discipline. For the individual researcher, it calls for skills and experience that can be associated with engaged scholarship. This paper explores tensions inherent in engaged scholarship, that arise during the quest to interact closely with professionals to ensure relevance and impact while living up to research quality criteria. The paper concludes that the individual researcher in a field such as PSM is easily left with guidelines that point in multiple directions regarding personal achievement and institutional merits. Highlights: Input from the PSM community on what is needed in order to survive and prosper as an engaged researcher. Introduction to the concept mapping methodology. The individual researcher is affected by a multitude of influencers, leading to tensions. Five key features of ES in PSM are: academic citizenship, community, publications, company relations and funding and support.